Fusobacterium nucleatum Causes Microbial Dysbiosis and Exacerbates Visceral Hypersensitivity in a Colonization-Independent Manner - Gu, Xiang; Song, Li-jin; Li, Li-xiang; Liu, Tong; Zhang, Ming-ming; Li, Zhen; Wang, Peng; Li, Ming; Zuo, Xiu-li (Frontiers in Microbiology, 2020)
Background Microbial dysbiosis is closely associated with visceral hypersensitivity and is involved in the pathogenesis of irritable bowel syndrome (IBS), but the specific strains that play a key role have yet to be identified. Previous bioinformatic studies have demonstrated that Fusobacterium is a shared microbial feature between IBS patients and maternal separation (MS)-stressed rats. In this study, we assessed the potential role of Fusobacterium nucleatum (F. nucleatum) in the pathogenesis of IBS. Methods Fecal samples of patients with diarrhea predominant-IBS (IBS-D) and healthy controls were obtained. MS rat model was established to receive gavage of either F. nucleatum or normal saline. Visceral sensitivity was evaluated through colorectal distension test, and fecal microbiota was analyzed by 16S rRNA gene sequencing. F. nucleatum-specific IgA levels in fecal supernatants were assessed by western blotting. The antigen reacted with the specific IgA of F. nucleatum was identified by mass spectrometry and the construction of a recombinant Escherichia coli BL21 (DE3). Results IBS-D patients showed a lower Shannon index and a higher abundance of Fusobacterium. The F. nucleatum-gavage was shown to exacerbate visceral hypersensitivity in MS rats, with both the F. nucleatum-gavage and MS causing a decreased Shannon index and a clear segregation of fecal microbiota. In addition, specific IgA against F. nucleatum was detected in fecal supernatants of both the F. nucleatum gavaged rats and the IBS-D patients. The FomA protein, which is a major outer membrane protein of F. nucleatum, was confirmed to react with the specific IgA of F. nucleatum in fecal supernatants. Conclusions Fusobacterium increased significantly in IBS-D patients, and F. nucleatum was involved in the pathogenesis of IBS by causing microbial dysbiosis and exacerbating visceral hypersensitivity in a colonization-independent manner. Meanwhile, F. nucleatum was found to induce an increase of specific secretory IgA through FomA.